Fetal ultrasound anatomy and morphometric parameters of the fibula - Komar , T.V.; Khmara , T.V.; Khodan , A.G.; Halaturnyk , I.B.; Kovalchuk , P.Ye. (Морфологія / Morphologia / Morfologìâ, 2023)
Objective. Today, it is impossible to imagine the effective work of obstetricians without using ultrasound examinations. The assessment of skeletal parameters is crucial for the early detection of fetal growth retardation, congenital malformations. Biparietal size, head circumference, abdominal circumference, and femur length are measured during a routine ultrasound. However, if there is any suspicion of any skeletal abnormality or intrauterine growth retardation, other long tubular bones should be additionally measured. The purpose of the research was to investigate the morphometric parameters of the length of the right and left fibula bones and to establish correlations between the lengths of the right and left fibula bones and the length of the corresponding lower limb during the fetal period of human development and the parietal-coccygeal length of the fetus. Methods. Ultrasound of the leg bones of 30 human fetuses was performed by the agreement on cooperation between "YUZKO MEDICAL CENTER" and the institution of higher education, Bukovynian State Medical University. A morphometric study was carried out on specimens of the lower extremities of 39 human fetuses of 81.0-375.0 mm parietal-coccygeal length. Statistical calculations were carried out using the built-in capabilities of MS Excel. The results. From the 4th to the 10th month of fetal stage, the length of the right fibula grows 2.66 times (from 23.90±2.29 mm to 63.63±1.04 mm). It is worth noting that the length of the left fibula also increases by 2.66 times - from 24.09±1.58 mm to 64.1±0.87 mm, respectively. Conclusion. Analysis of the obtained data indicates relatively uniform growth of the length of the right and left fibula bones during the fetal period of human ontogenesis. Two periods of intense growth in the length of the right and left fibula bones in human fetuses were found: from the end of the 5th to the end of the 6th month and from the end of the 7th to the middle of the 8th month. The slow increase in the length of the fibula bones occurs in the 4th and 9-10 months of fetal development.